2017
DOI: 10.4067/s0718-95162017005000035
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of soil fertility using the Rasch model

Abstract: A quantification of the overall soil fertililty potential should integrate the main soil physical and chemical properties, with different units. The formulation of the Rasch model is proposed as an instrument to measure soil fertility potential, integrating 11 soil properties (clay, silt and sand content, organic matter -OM-, pH, total nitrogen -TN-, available phosphorus -AP-and potassium -AK-, cation exchange capacity -CEC-, and deep -ECdand shallow -ECs-soil apparent electrical conductivity, 0-90 and 0-30 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…These properties may have influenced the better sandy clay loam performance in maize yield. Moral and Rebollo [ 48 ] suggested that these properties may have a high influence on soil fertility.…”
Section: Discussionmentioning
confidence: 99%
“…These properties may have influenced the better sandy clay loam performance in maize yield. Moral and Rebollo [ 48 ] suggested that these properties may have a high influence on soil fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Moral and Rebollo [75] characterized soil fertility using the Rasch Model and concluded that particle-size distribution, electrical conductivity, cation exchange capacity, pH, organic matter, and the primary nutrients (N, P, and K) are the most influential variables on soil fertility. They maintained that soil texture and pH influenced the extent to which nutrients are available to plants.…”
Section: Effects Of Soil Type On the Maize Growth Attributes And Dry ...mentioning
confidence: 99%
“…This fact was more less confirmed in this research. Moral and Rebollo [50] deem the CEC a sensitive indicator for determining the soil's nutrient holding capacity, fertility, and long-term productivity. This parameter can be an additional characteristic to evaluate SOM quality in various ecosystems (fields, forests, etc.).…”
Section: Discussionmentioning
confidence: 99%